Effects of Three Artificial Diets on Life History Parameters of the Ladybird Beetle Stethorus gilvifrons, a Predator of Tetranychid Mites - Jafar Ebrahimifar; Parviz Shishehbor; Arash Rasekh; Seyed Ali Hemmati; Eric W. Riddick (Insects, 2020)
Background: The ladybird beetle Stethorus gilvifrons (Mulsant) is an important natural enemy of tetranychid mites and functions as a biological control of these plant pests. The development, survival and reproduction of S. gilvifrons were studied when fed on three artificial diets. The components of the artificial diet that S. gilvifrons could be reared successfully on for one generation with no use of tetranychid mites were examined. Methods: Artificial diets consisted of sucrose, honey, royal jelly, agar, yeast, date palm pollen supplemented in different diets with hen’s egg yolk (AD1, as basic diet), Ephestia kuehniella Zeller eggs (AD2), or E. kuehniella eggs and 2,4-dihydroxybenzoic acid (AD3). Results: Adults and larvae of Stethorusgilvifrons fed on AD1 had a shorter immature development and preoviposition periods than those fed on AD2 and AD3. The total number of deposited eggs was significantly higher for the females fed on AD3 than on the other diets. The intrinsic rate of increase (r) of S. gilvifrons was highest on AD3, followed by AD2, and AD1. Conclusion: Stethorus gilvifrons performed best on AD3, indicating the potential of this artificial diet for the mass rearing of this important predatory ladybird beetle.